Evaluation of Human Milk Microbiota by 16S rRNA Gene Next-Generation Sequencing (NGS) and Cultivation/MALDI-TOF Mass Spectrometry Identification - Treven, Primož; Mahnič, Aleksander; Rupnik, Maja; Golob, Majda; Pirš, Tina; Matijašić, Bojana Bogovič; Lorbeg, Petra Mohar (Frontiers in Microbiology, 2019)
The aim of the present study was to characterise human milk microbiota (HMM) with 16S rRNA gene amplicon next-generation sequencing and cultivation/MALDI-TOF mass spectrometry identification approaches. We analysed 31 human milk samples from healthy Slovenian mothers. To check the accuracy of MALDI-TOF MS identification, several colonies representing most abundant genera and those, which could not be reliably identified by MALDI-TOF, were subjected to Sanger sequencing of their 16S rRNA gene. We showed that cultivation/MALDI-TOF MS was suitable tool for culture-dependent determination of HMM. With both approaches, Staphylococcus and Streptococcus were found predominant genera in HMM and the abundance of Staphylococcus was associated with decreased microbial diversity. In addition, we characterised factors that might influence HMM. The use of a breast pump was significantly associated with composition of HMM, lower microbial load and higher abundance of cultivable staphylococci. Moreover, our study suggests that administration of probiotics to the suckling infant might influence HMM by increased abundance of lactobacilli and the presence of viable probiotic bacteria in human milk. However, since our study was observational with relatively small sample size, more targeted studies are needed to study possible transfer of probiotics to the mammary gland via an external route and the physiological relevance of these events.